2016
DOI: 10.1245/s10434-016-5243-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Lymph Node Status for Patients With Gallbladder Cancer: A Multi-Institutional Study

Abstract: Background Although the American Joint Committee on Cancer (AJCC) classification is the most accepted lymph node (LN) staging system for gallbladder adenocarcinoma (GBA), other LN prognostic schemes have been proposed. This study sought to define the performance of the AJCC LN staging system relative to the number of metastatic LNs (NMLN), the log odds of metastatic LN (LODDS), and the LN ratio (LNR). Methods Patients who underwent curative-intent resection for GBA between 2000 and 2015 were identified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…A number of factors are associated with outcome in incidental gallbladder cancer. Among the most important is the ability to achieve an R0 resection, whereas both a higher T category and the presence of lymph node metastasis are strong predictors of poor survival. Several attempts at refining prognostication have been entertained, with a Gallbladder Cancer Predictive Risk (GBPR) score developed from a multicentre series of incidental gallbladder cancers.…”
Section: Resultsmentioning
confidence: 99%
“…A number of factors are associated with outcome in incidental gallbladder cancer. Among the most important is the ability to achieve an R0 resection, whereas both a higher T category and the presence of lymph node metastasis are strong predictors of poor survival. Several attempts at refining prognostication have been entertained, with a Gallbladder Cancer Predictive Risk (GBPR) score developed from a multicentre series of incidental gallbladder cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Several other LN staging schemas have been proposed to evaluate the impact of TLNC and N1 disease on long‐term outcomes. In fact, our own group previously demonstrated that LODDS performed better than the AJCC LN staging system in terms of prognostic discrimination among patient with GBC . Other authors have advocated that the minimum number of LN resected to identify metastatic LNs and, thus properly stage the disease, could be derived from the LODDS distribution .…”
Section: Discussionmentioning
confidence: 99%
“…own group previously demonstrated that LODDS performed better than the AJCC LN staging system in terms of prognostic discrimination among patient with GBC. 24 Other authors have advocated that the minimum number of LN resected to identify metastatic LNs and, thus properly stage the disease, could be derived from the LODDS distribution. 17 To this point, we compared results from the machinelearning approach with the LODDS approach to identify the optimal range of LNs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Moreover, log odds ratio (LODDS), defined as the log of the ratio between the number of positive lymph nodes (PLNs) and the number of negative lymph nodes, has been proved effective in predicting the prognosis of patients with head and neck, breast, gallbladder, gastric, and colorectal cancers. [10][11][12][13][14] Whether LODDS can be used as a prognostic index of nonÀsmall cell lung cancer, however, is still unclear.…”
Section: See Editorial Commentary Page 710mentioning
confidence: 99%